ASPEK-ASPEK YURIDIS PERJANJIAN PENGIKATAN JUAL BELI PROPERTI MENURUT KEPUTUSAN MENTERI NEGARA PERUMAHAN RAKYAT NOMOR 09/KPTS/M/1995 TENTANG PEDOMAN PENGIKATAN JUAL BELI RUMAH ( STUDI KASUS PADA PT. SARWO INDAH KABUPATEN SLEMAN) - , ISMALIAH, Pitaya, SET., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the implementation of sale and purchase property binding treaty at PT Sarwo Indah in Sleman Regency in terms of the Decree of Public Housing Minister Number 09/KPTS/M/1995. This study is a combination of juridical empirical research - with emphasis on field and literature legal research methods such as performed by examining library materials or secondary data for later comparison with the statutory provisions in force. Data collection techniques used library research and field research. The result analytical method used is the qualitative methods which explaining social reality encountered in the field. The results showed that the implementation of the sale and purchase property binding treaty in the Sleman Regency still violated the Decree of the Minister of Public Housing No. 09/KPTS/M/1995. Beside, it also found that the sale and purchase property binding treaty has no legal power to be used as a basic for the fulfillment of the right to sue the seller who does not fulfill his achievement to submit certificate as ownership evidence of home that have been paid. The sale and purchase property binding treaty are usually only made in front of the company's legal, so it can not be used to prosecute certificate. As for who has the legal power to demand the fulfillment of the right of the buyer to obtain a certificate for the land and the house already paid is sale and purchase property binding treaty which made in front of PPAT (official land deed maker).